1998
DOI: 10.1017/s0373463397007595
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Discrimination Learning in Rainbow Trout (Oncorhynchus mykiss)

Abstract: Although conditioning techniques are the most powerful way to study behavioural responses by animals to external stimuli, the magnetic sense has proved surprisingly resistant to conditioning approaches. This study demonstrated learned discrimination of magnetic field intensity stimuli by a new species, the rainbow trout (Oncorhynchus mykiss). In a unitary conditioned discrimination technique, four juvenile rainbow trout were trained to strike a target at the end of a response bar in anticipation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The other line of evidence for magnetosensation is based on conditioning experiments. The yellowfin tuna ( Thunnus albacares ) [12]), the rainbow trout [13], [14], the zebrafish ( Danio rerio ) and the Mozambique Tilapia ( Tilapia zillii ) [15]) could be trained to discriminate between two magnetic fields of different intensities. In contrast to that, conditioning to magnetic stimuli failed in the atlantic salmon ( Salmo salar , [16]), the goldfish [17], and the land-locked sockeye salmon [18].…”
Section: Introductionmentioning
confidence: 99%
“…The other line of evidence for magnetosensation is based on conditioning experiments. The yellowfin tuna ( Thunnus albacares ) [12]), the rainbow trout [13], [14], the zebrafish ( Danio rerio ) and the Mozambique Tilapia ( Tilapia zillii ) [15]) could be trained to discriminate between two magnetic fields of different intensities. In contrast to that, conditioning to magnetic stimuli failed in the atlantic salmon ( Salmo salar , [16]), the goldfish [17], and the land-locked sockeye salmon [18].…”
Section: Introductionmentioning
confidence: 99%
“…Trout appear to have a magnetic sense, as demonstrated in the laboratory by responsive behaviors modified with magnetic fields (Walker et al 1997). Furthermore, they can detect spatially distinct magnetic stimuli (Haugh et al 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Magnetic conditioning studies with a variety of other species have since then demonstrated sensitivity to magnetic fields in both invertebrates and vertebrates (honey bee: Walker and Bitterman, 1985; yellow-fin tuna: Walker, 1984; rainbow trout: Walker et al , 1997; Haugh and Walker, 1998; short-tailed stingray: Walker et al , 2003). They also revealed some unexpected requirements to be critical for magnetic conditioning to succeed.…”
Section: Conditioning As An Approach To Orientation Behaviourmentioning
confidence: 99%